Adoptively transferred experimental allergic encephalomyelitis in chimeric rats: identification of transferred cells in the lesions of the central nervous system. - Matsumoto, Y (1988)
Experimental allergic encephalomyelitis (EAE) was induced by adoptive transfer of myelin basic protein (MBP)-activated LEW spleen cells into (LEW x PVG/c) F1----LEW chimeras. By double-immunofluorescent staining using OX27, which is specific for RT1c, and monoclonal antibodies (mAb) against various T-cell antigens (TAg), inflammatory cells in the lesions of the central nervous system (CNS) were categorized into MBP-activated and transferred LEW T cells (TAg+ OX27-), accompanying T cells (TAg+ OX27+) of chimera origin and non-T cells (TAg- OX27+). Examination of the lesions at various stages of EAE revealed that transferred OX19 (CD5)+ T cells accounted for 46% of the total number of inflammatory cells at the preclinical stage, became reduced to 23% at the clinical stage and recovered to a level between those of the preclinical and clinical stages at the recovery stage. In parenchymal infiltrates, 93% of the total T cells were transferred cells at the preclinical stage, whereas 66% were present in perivascular aggregates. At the clinical stage, the proportion of transferred T cells in the parenchyma was not different from that in the perivascular cuffs. At the recovery stage, the proportion of transferred T cells in the parenchyma was increased. Collectively, MBP-activated and transferred T cells first appeared in the CNS parenchyma followed by infiltration of T and non-T cells of recipient (chimera) origin. All these inflammatory cells formed the lesions of full-blown EAE. At the recovery stage, inflammatory cells decreased in number in all the compartments of the CNS. Transferred T cells formed the major proportion of parenchymal infiltrates at this stage. These findings strongly suggest that transferred T cells remain in the CNS parenchyma longer than cells of chimera origin and that antigen-activated T cells have well-expressed CNS-homing activity.